A Nonlethal Genetic Assay for Discriminating Sex in Brook Trout. (29th April 2021) - Webster, N.; Price, S.; Gowan, C.; Coster, S. S.
Abstract: Identifying sex in salmonids using nonlethal methods is valuable for controlled breeding in aquaculture and understanding behavior and dispersal for conservation. Although salmonids are male heterogametic, genetic sex identification has been problematic because a specific sex determination locus has been elusive. We implemented a blind analysis to identify sex in Brook Trout Salvelinus fontinalis using genetic primers (sdY) developed for Brown Trout Salmo trutta along with cytochrome c oxidase subunit I (COI_BT1) as an internal control. Fin clips were taken from 35 Brook Trout and analyzed via PCR and gel electrophoresis, and fish were simultaneously sacrificed and dissected to identify sex via gonads. The genetic and phenotypic analysis matched in 97% of the Brook Trout that were sampled, suggesting that this primer combination is successful in genetic sex determination. The ability to sex Brook Trout genetically will allow scientists to observe the difference in male and female Brook Trout behavior in the lab and natural stream ecosystems without using lethal methods.